Employee perceptions of and reactions to global talent management: A case study - Siuko, Maikki (My University, 2016)
Talent management (TM) has become increasingly important in multinational corporations (MNCs). Talent pool members are at the core of TM activities, and their perceptions of and reactions to TM are likely to have a great impact on the effectiveness of talent programs. Therefore the employee perspective on TM should be better understood. The purpose of the thesis is to find out how those individuals that have been identified as talent perceive the TM process, and how they react to talent pool membership. Two research questions were formed, with the objective of increasing the understanding of what it means to be talent, how the communication around talent issues is perceived, and what implications talent pool membership has for employees. This thesis uses a qualitative case study method. The empirical data was collected in ten semi-structured interviews with individuals that have been formally identified as talent in a large MNC. The interviews were conducted within a single case organization in order to minimize the effects of differences in TM practices between companies. The data was analyzed through content analysis. The main findings of the study indicate that TM strengthens the organization-employee relationship, providing mutual benefits. However, also feelings of confusion and injustice emerged. It is suggested that increasing the level of communication and transparency gives rise to more positive employee reactions and therefore, better organizational outcomes.
Keywords: talent management; global talent management; employee perceptions; perceived justice; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|